FACEBOOK EWOM MARKETING STRATEGY: A SOCIAL SUPPORT THEORY PERSPECTIVE - Luo, Margaret Meiling; Chen, Min Wen; Chea, Sophea (PEOPLE: International Journal of Social Sciences, 2020)
Today, social media is a major communication medium for online users. Along the use of social media, electronic word-of-mouth (EWOM) is a common user behavior. To understating the Facebook marketing and form marketing strategy has become an increasingly important issue. Facebook ranks at top one social medium where the posts on food and dining ranks at top 5 topics. To understand the EWOM behavior, this study investigates that positive and negative EWOM over Facebook. Both social exchange theory and social support theory are applied in our study. The results suggest that trust and social support are the major reason that influence customer satisfaction and dissatisfaction of Facebook, which in turn influence the positive and negative EWOM intention respectively. The theoretical contribution of our study lies in the application of two social theories in online context. The empirical contribution is to provide our findings to e-retailers to create positive EWOM meanwhile to avoid negative EWOM. The results of our study benefits e-retailers to build up positive reputations and form marketing strategy for business growth.